The ontology of men and women"s relationships in contemporary African ecclesiology: Towards a theology of authority-submission in the church - Mati, Ali (HTS teologiese studies, 2022)
With the active involvement of women in the church and home, there is a need to study God’s design for the relationship between men and women. In reaffirming the divine order of this relationship, discussing the biblical gendered roles has been one of the major contending issues. So emerging ecclesiologies in Africa are beginning to challenge the traditional understanding of male headship in the church. Therefore, the article argues that the ontology of men and women’s relationship provides a better framework for understanding the nature of authority and submission in the church. This article states fairly the biblical foundation for the ontology of male and female relationship in the church from both the complementarian and egalitarian views. Also, this article presents the male and female relationship in contemporary African ecclesiology. Furthermore, the article contends that the application of the biblical foundation for the relationship between men and women provides a strong framework for authority and submission in the church, which reaffirms the male headship. The goal of the article is to use the biblical framework for the ontology of the relationships between men and women to propose a theology of authority and submission in the church without undermining the nature and worth of men and women, who are both created in the image and likeness of God. A qualitative methodology was used for this article, which integrates both primary and secondary sources to delineate the thesis of the study.Contribution: This article contributes to the area of ecclesiology in Africa, which shows that the theology of the church is relevant for engaging cutting-edge issues, such as gender studies, human relations and personhood. It explains the influence and implications of the ontology of gender relationship on authority and submission in the church to affirm human dignity and equality in the church.